Association of β-blocker use with survival and pulmonary function in patients with chronic obstructive pulmonary and cardiovascular disease: a systematic review and meta-analysis. (19th November 2020) - Yang, Yan-Li; Xiang, Zi-Jian; Yang, Jing-Hua; Wang, Wen-Jie; Xu, Zhi-Chun; Xiang, Ruo-Lan
Abstract: Aims: The aim of this study was to clarify the effect of β-blockers (BBs) on respiratory function and survival in patients with chronic obstructive pulmonary disease with cardiovascular disease (CVD), as well as the difference between the effects of cardioselective and noncardioselective BBs. Methods and results: We searched for relevant literature in four electronic databases, namely, PubMed, EMBASE, Cochrane Library, and Web of Science, and compared the differences in various survival indicators between patients with chronic obstructive pulmonary disease taking BBs and those not taking BBs. Forty-nine studies were included, with a total sample size of 670 594. Among these, 12 studies were randomized controlled trials (RCTs; seven crossover and five parallel RCTs) and 37 studies were observational (including four post hoc analyses of data from RCTs). The hazard ratios (HRs) of chronic obstructive pulmonary disease exacerbation between patients with chronic obstructive pulmonary disease who were not treated with BBs and those who were treated with BBs, cardioselective BBs, and noncardioselective BBs were 0.77 [95% confidence interval (CI) 0.67, 0.89], 0.72 [95% CI 0.56, 0.94], and 0.98 [95% CI 0.71, 1.34, respectively] (HRs <1 indicate favouring BB therapy). The HRs of all-cause mortality between patients with chronic obstructive pulmonary disease who were not treated with BBs and those who were treated with BBs, cardioselective BBs, and noncardioselective BBs were 0.70 [95% CI 0.59, 0.83], 0.60 [95% CI 0.48, 0.76], and 0.74 [95% CI 0.60, 0.90], respectively (HRs <1 indicate favouring BB therapy). Patients with Chronic obstructive pulmonary disease treated with cardioselective BBs showed no difference in ventilation effect after the use of an agonist, in comparison with placebo. The difference in mean change in forced expiratory volume in 1 s was 0.06 [95% CI −0.02, 0.14]. Conclusion: The use of BBs in patients with chronic obstructive pulmonary disease is not only safe but also reduces their all-cause and in-hospital mortality. Cardioselective BBs may even reduce chronic obstructive pulmonary disease exacerbations. In addition, cardioselective BBs do not affect the action of bronchodilators. Importantly, BBs reduce the heart rate acceleration caused by bronchodilators. BBs should be prescribed freely when indicated in patients with chronic obstructive pulmonary disease and heart disease.